UJI AKTIVITAS ANTIHIPERGLIKEMIA EKSTRAK ETANOL KULIT BATANG SENGKUANG Dracontomelon dao (Blanco) Merr & Rolfe TERHADAP MENCIT PUTIH (Mus musculus) JANTAN GALUR SWISS WEBSTER - inderiyani inderiyani; Sulastri Herdaningsih; Ihsanul Arief Arief (Jurnal Komunitas Farmasi Nasional, 2022)
Diabetes mellitus (DM) is a serious chronic disease that occurs when the pancreas does not produce enough insulin or when the body cannot effectively use the insulin it produces. Sengkuang Dracontomelon dao (Blanco) Merr & Rofle has the potential as an alternative treatment for DM because it contains secondary metabolites in the form of alkaloids, tannins and flavonoids which have antihyperglycemic properties. This study aims to determine the antihyperglycemic activity of sengkuang stem bark against male white mice. Sengkuang bark is processed into simplicia and then macerated using 96% ethanol as a solvent. Then the extract was used to test antihyperglycemic activity by measuring initial glucose levels with a glucose test strip and given a test solution in the form of 0.5% Na.CMC suspension; glibenclamide 65 mg/kgbb; ethanol extract of sengkuang stem bark dose of 100 mg/kgbb; 200 mg/kgbb and 400 mg/kgbb. Then the test animals were induced with glucose 75 gram/kgbb and blood glucose levels were measured at 0, 30, 60, 90, 120, 150 and 180 minutes. The results showed that the ethanol extract of sengkuang bark at a dose of 400 mg/kgbb had activity as antihyperglycemic indicated by a significant difference with the negative control group. Keywords : Antihyperglycemia, diabetes mellitus, ethanol extract of sengkuang bark, Dracontomelon dao (Blanco) Merr & Rofle